Analisis Budaya Desain Masjid Zaman Dahulu dan Sekarang: Studi Kasus Masjid Cipaganti, Al-Jabbar, Kota Bandung - Ahmad Bayhaqi; Irsad Fadil; Muhammad Rafa Alifian Zean; Sri Hasniar Rahayu; Edi Suresman (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Cultural influences have changed the design of mosques in the past and present, causing differences in some respects. This research focuses on Bandung City, namely on Cipaganti and Al-Jabbar mosques as representations of the past and present. Using a qualitative and comparative approach, data was collected through triangulation of interviews, observation, and documentation. The analysis refers to the theory of Islamic Architecture Typology including architectural aspects (typology of space and form) and contextual aspects (function and style). The findings show that the Cipaganti and Al-Jabbar Mosque designs show significant differences in the development of Islamic culture in Bandung. Cipaganti has many traditional elements and local culture, while Al-Jabbar adopts a modern and multifunctional approach, creating a broader social and educational center.